2006
DOI: 10.3759/tropics.15.411
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of water at the upper reaches of the Sebangau River, Central Kalimantan, Indonesia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Tropical peatland waters can have very high DOC concentrations (Miyamoto et al , 2009; Yule & Gomez, 2009) and, together with lower amounts of particulate organic carbon (POC) (cf. Yoshioka et al , 2002), this carbon is exported in substantial amounts (Tachibana et al , 2006; Alkhatib et al , 2007; Baum et al , 2007; Rixen et al , 2008; cf. Hope et al , 1994; Harrison et al , 2005) and rapidly decomposed (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical peatland waters can have very high DOC concentrations (Miyamoto et al , 2009; Yule & Gomez, 2009) and, together with lower amounts of particulate organic carbon (POC) (cf. Yoshioka et al , 2002), this carbon is exported in substantial amounts (Tachibana et al , 2006; Alkhatib et al , 2007; Baum et al , 2007; Rixen et al , 2008; cf. Hope et al , 1994; Harrison et al , 2005) and rapidly decomposed (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Whole catchments of the Sebangau River are covered by peatlands, and hence river water contains a high concentration of humic substances (dark brown color) and background pH is 3.5-4.0. Tachibana et al (2003) reported that maximum water fl ux of Sebangau River is 50 m 3 /s from December to February and the minimum is 5 m 3 /s from June to September at Kya. Water fl ux of the lower basin of the Sebangau River is not reported.…”
Section: Study Sites and Methodsmentioning
confidence: 98%
“…The periodic fluctuation of cation concentrations during this transition period is presumably due to the sudden increase of water discharge that might be bringing more organic inputs to the system. B I O DI VE RS I T A S 19 (4): 1181-1185, July 2018 1182 Despite the fact that this humic floodplain ecosystem of Palangka Raya is physicochemically poor in nutrient content (Tachibana et al 2003), it supports high diversity and production of inland fisheries. There were more than 300 freshwater fish species had been recorded in Central Kalimantan Province (Anon 2010).…”
Section: Introductionmentioning
confidence: 99%